Predictors of maternal mortality by COVID-19: an integrative review (Research, Society and Development, 2021)
Objective: to review scientific production on factors related to maternal mortality caused by COVID-19 infection. Methods: This is an integrative review. The survey of publications took place in May 2021 using the descriptors “Maternal Mortality”, “COVID-19” and “Pregnancy”, in the Virtual Health Library (VHL). After analyzing the studies, four articles were included as the final sample. Results: Complications and evolution to death in pregnant women contaminated by COVID-19 are linked to the association of physiological changes in the pregnancy process, comorbidities such as cardiovascular disease, obesity and diabetes; inadequate assistance in prenatal, postpartum and advanced service (ICU and ventilatory support), in addition to racial issues. Conclusion: The identification of some factors that aggravate the health status of pregnant women contaminated by COVID-19, which can lead to fatal complications, since the physiological and anatomical changes of the gestational period, combined with comorbidities resulting from chronic diseases, predispose to greater risk of hospitalizations. Continuing education actions are needed so that the service is provided in a specialized, effective and equitable manner, in order to mitigate the risk of death in pregnant women.